Proceedings of the 36th International Conference on Software Engineering 2014
DOI: 10.1145/2568225.2568295
|View full text |Cite
|
Sign up to set email alerts
|

Mining billions of AST nodes to study actual and potential usage of Java language features

Abstract: Programming languages evolve over time, adding additional language features to simplify common tasks and make the language easier to use. For example, the Java Language Specification has four editions and is currently drafting a fifth. While the addition of language features is driven by an assumed need by the community (often with direct requests for such features), there is little empirical evidence demonstrating how these new features are adopted by developers once released. In this paper, we analyze over 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 32 publications
3
61
1
Order By: Relevance
“…Parnin et al have studied adoption of Java generics [70], Pinto et al studied concurrent programming constructs [71], and Dyer et al studied features prior to their official release [72]. Similar studies have also been conducted, e.g., for C# [73] and PHP [60].…”
Section: Related Workmentioning
confidence: 99%
“…Parnin et al have studied adoption of Java generics [70], Pinto et al studied concurrent programming constructs [71], and Dyer et al studied features prior to their official release [72]. Similar studies have also been conducted, e.g., for C# [73] and PHP [60].…”
Section: Related Workmentioning
confidence: 99%
“…Dyer et al, in their large scale investigation of Java projects hosted on SourceForge 12 , found that new features are used by developers before the official release of the specification, taking advantage of the beta/pre-releases [41]. More likely than not, also the developers who worked on the projects included in the baseline corpus, adopted new language features during the development process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dyer et al found also that the majority of newly introduced language features are rarely used by developers [41], with few meaningful exception. According to Qiu et al [42], who conducted a large-scale study on the use of Java constructs, the distribution of syntactic rules usage is Zipfian, with 20% of the most-used rules accounting for 85% of all rule usage, whereas the 65% of the leastused rules is used less than 5%.…”
Section: Discussionmentioning
confidence: 99%
“…They extracted this information from an XML representation (i.e., srcML) of the source code of subject systems. Dyer et al [23] conducted a very largescale study on 31K open-source Java projects to find usages of new Java language features over time. This is done on the Abstract Syntax Tree (i.e., AST) of the source code of the subject systems.…”
Section: Related Workmentioning
confidence: 99%